Generalized derivation modulo the ideal of all compact operators - Salah Mecheri; Ahmed Bachir (International Journal of Mathematics and Mathematical Sciences)
We give some results concerning the orthogonality of the range and the kernel of a generalized derivation modulo the ideal of all compact operators.